2016
DOI: 10.1016/j.calphad.2016.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Computational study of atomic mobility in hcp Mg–Al–Zn ternary alloys

Abstract: The experimental data in the literature for the hcp phase of the Mg-Al-Zn ternary system have been critically reviewed. Based on the concentration profiles from the literature, the diffusion coefficients have been re-extracted using the Hall method for the impurity diffusion, and the Sauer-Freise and the Whittle-Green strategies for interdiffusion coefficients in binary and ternary systems, respectively. Moreover, extra interdiffusion coefficients were obtained from the "Darken-type" couples, which present rel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 32 publications
4
12
0
Order By: Relevance
“…The Al impurity diffusion coefficients within the basal plane, Fig. 11a, together with the experimental impurity diffusion coefficients obtained from Mg polycrystals [13][14][15]25,40] and single crystals along the basal plane and the c axis [27]. The present results are consistent with the experimental values obtained by Brennan [15] and Kammerer [13] (a) (b) using polycrystalline Mg-Al diffusion-couples and also with the first principles calculations of Zhou [29].…”
Section: Anisotropic Impurity Diffusion Coefficientssupporting
confidence: 89%
See 1 more Smart Citation
“…The Al impurity diffusion coefficients within the basal plane, Fig. 11a, together with the experimental impurity diffusion coefficients obtained from Mg polycrystals [13][14][15]25,40] and single crystals along the basal plane and the c axis [27]. The present results are consistent with the experimental values obtained by Brennan [15] and Kammerer [13] (a) (b) using polycrystalline Mg-Al diffusion-couples and also with the first principles calculations of Zhou [29].…”
Section: Anisotropic Impurity Diffusion Coefficientssupporting
confidence: 89%
“…11 (a) The Arrhenius expression of the Al impurity diffusion coefficient in pure Mg. The different symbols stands for experimental results in the literature for polycrystals [13][14][15]27,40] and single crystals [27]. The solid lines stand for the predicted Al impurity diffusion coefficients perpendicular to the c axis, while the dashed lines represent the predictions along the c axis.…”
Section: Anisotropic Impurity Diffusion Coefficientsmentioning
confidence: 99%
“…It has been argued that the limited precipitation hardening of Mg-Al alloys occurs because most of the precipitates exhibit Burgers OR and lay parallel to the basal plane, and this orientation is the least efficient to block basal slip [12]. It was also suggested that the precipitate distribution is relative coarse because of the high diffusion rate of Al atoms in the Mg matrix [43]. Finally, based on the Orowan model, it was proposed that rod-shaped precipitates that grow perpendicular to the basal plane with Crawley OR ({0001} M g {111} β ; 1210 M g 112 β ) are more efficient because they intersect a larger number of basal planes for a given precipitate volume fraction [42,12,16,44].…”
Section: Background On Precipitate-strengthened Mg-al Alloysmentioning
confidence: 99%
“…The impurity diffusion of Ga in hcp-Mg is further compared in Fig. 3(b) with various alloying elements (inc. Al, Ca, Ga, Sn, Y, Mn and Zn) [6][7][8]40] with a reference to the Mg self-diffusion. Apparently, Ga is much alike Zn and diffuses faster compared to the self-diffusion of Mg, while Al is among those slower impurity diffusers like Sn and Y.…”
Section: Diffusion and Mobility Of Mg-ga Alloysmentioning
confidence: 99%
“…The experimental results[36] are shown as symbols and the first-principles calculations[37] are shown as solid lines for comparison. (b) Impurity diffusion coefficients of solute X (Al, Ca, Ga, Sn, Y, Mn and Zn)[6][7][8]40] are compared with reference to the Mg self-diffusion coefficient.…”
mentioning
confidence: 99%